Mose im Judentum des Zweiten Tempels. Rezeption, Fortschreibung und Aktualisierung einer alttestamentlichen Gestalt - Paganini, Simone 1972- (2013)
The reception of phrases, themes, and motifs has a significant impact on the hermeneutics of the final text. It is possible to observe trends, convergences and differences that can help to describe the socio-cultural background of the (ancient) recipients. In order to show these developments, this study focuses on the various ways the figure of Moses is described in Second Temple Jewish Literature. By comparing these texts with the way Moses is employed in the Pentateuch and the rest of the Old Testament, it is possible to identify a paradigmatic shift in the reception of this figure. This testifies to the hermeneutical freedom employed by interpreters of biblical texts in late Second Temple Judaism, as they distanced themselves - even if in different ways - more and more from the “biblical” Moses. Such a development is true for texts with Palestinian origin as well as texts traditionally ascribed to the Jewish diaspora.
Keywords: Mose -- Biblische Person; Rezeption